2020
DOI: 10.1177/1044207320949962
|View full text |Cite
|
Sign up to set email alerts
|

Application of the World Café to Disability Issues: A Systematic Review

Abstract: Improving outcomes for individuals with disabilities requires collaborative and comprehensive efforts to address barriers at the community level. The World Café is often advocated as a community-engagement approach for bringing an assortment of community members (e.g., professionals, civic leaders, families, neighbors) into solutions-focused discussions about pressing local issues. This systematic review examined how the World Café has been applied specifically to disability issues. A literature search yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…World Cafés are a flexible participatory method that have been used widely to explore issues that are important to communities [ 11 ] and are an inclusive tool to engage with diverse communities [ 12 ]. Central to the approach is fostering an environment where communities involved can have “conversations that matter”, through creating an environment where people can communicate constructively, enabling access to “collective intelligence and creating innovative possibilities for action” (p. 3) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…World Cafés are a flexible participatory method that have been used widely to explore issues that are important to communities [ 11 ] and are an inclusive tool to engage with diverse communities [ 12 ]. Central to the approach is fostering an environment where communities involved can have “conversations that matter”, through creating an environment where people can communicate constructively, enabling access to “collective intelligence and creating innovative possibilities for action” (p. 3) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This theme informs our efforts to expand and sustain engagement with stakeholder groups. Our face-to-face meetings broadly reflected a useful structure for facilitating engagement called community conversations ( 33 , 34 ). We found that the structured but flexible approach of bringing diverse groups of stakeholders together and engaging them in complex topics involving local and systemic factors was a highly productive process.…”
Section: Discussionmentioning
confidence: 99%
“…Best practices in self-direction: what we've learned Using a World Caf e format (Bumble and Carter, 2020), Match participants came to consensus on best practices to ensure self-direction is implemented effectively and in alignment with the values of self-determination and social justice. These best practices, described below, are implemented to varying degrees across the world.…”
Section: Experiences Of People Who Self-directmentioning
confidence: 99%